Proof: Do Variables At Unchanged 69
Let's prove the following theorem:
if the following are true:
- expression state at time 69 = "call_function_begin"
- Variables Map at time 69 = [ entry joe: (Python reference 0), [ ] ]
then Variables Map at time 70 = [ entry joe: (Python reference 0), [ ] ]
Proof:
Given
1 | expression state at time 69 = "call_function_begin" |
---|---|
2 | Variables Map at time 69 = [ entry joe: (Python reference 0), [ ] ] |
# | Claim | Reason |
---|---|---|
1 | Variables Map at time (69 + 1) = Variables Map at time 69 | if expression state at time 69 = "call_function_begin", then Variables Map at time (69 + 1) = Variables Map at time 69 |
2 | Variables Map at time (69 + 1) = [ entry joe: (Python reference 0), [ ] ] | if Variables Map at time (69 + 1) = Variables Map at time 69 and Variables Map at time 69 = [ entry joe: (Python reference 0), [ ] ], then Variables Map at time (69 + 1) = [ entry joe: (Python reference 0), [ ] ] |
3 | 69 + 1 = 70 | 69 + 1 = 70 |
4 | Variables Map at time (69 + 1) = Variables Map at time 70 | if 69 + 1 = 70, then Variables Map at time (69 + 1) = Variables Map at time 70 |
5 | Variables Map at time 70 = [ entry joe: (Python reference 0), [ ] ] | if Variables Map at time (69 + 1) = Variables Map at time 70 and Variables Map at time (69 + 1) = [ entry joe: (Python reference 0), [ ] ], then Variables Map at time 70 = [ entry joe: (Python reference 0), [ ] ] |
Comments
Please log in to add comments